Data-Driven Decision Making In Large Scale Production Planning - Christefa, Dea; Mawengkang, Herman; Zarlis, Muhammad (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Production planning is a very important part for a company in making the right decisions before carrying out production activities in order to obtain maximum profit with a minimum level of production costs. Production planning is defined as a process in producing goods and services within a certain period by considering resources such as labor, materials, machinery and etc. In this research, a production planning model is produced based on several variables and parameters that can assist in making production decisions